Mumps: MMR vaccination and genetic diversity of mumps virus, 2007–2011 in Catalonia, Spain - Barrabeig, Irene (BMC Infect Dis, 2019)
BACKGROUND: Mumps is a vaccine-preventable disease but outbreaks have been reported in persons vaccinated with two doses of MMR vaccine. The objective was to describe the demographic features, vaccination effectiveness and genetic mumps virus diversity among laboratory-confirmed cases between 2007 and 2011 in Catalonia. METHODS: Cases and outbreaks of mumps notified to the notifiable diseases system of Catalonia between 2007 and 2011 retrospectively registered were included. Public health care centres provided written immunization records to regional public health staff to determine the vaccination history. Saliva and serum specimens were collected from suspected cases for laboratory-confirmation using real-time reverse-transcriptase PCR (rtRT-PCR) or serological testing. Phylogenetic analysis of the complete SH gene (316 nucleotides) and complete coding HN protein (1749 nucleotides) sequences was made. Categorical variables were compared using the Chi-square or Fisher’s tests and continuous variables using the Student test. Vaccination effectiveness by number of MMR doses was estimated using the screening method. RESULTS: During the study period, 581 confirmed cases of mumps were notified (incidence rate 1.6 cases/100,000 persons-year), of which 60% were male. Three hundred sixty-four laboratory-confirmed cases were reported, of which 44% were confirmed by rtRT-PCR. Of the 289 laboratory-confirmed cases belonging to vaccination cohorts, 33.5% (97) had received one dose of MMR vaccine and 50% (145) two doses. Based on phylogenetic analyses of 316-nucleotide and 174-nucleotide SH sequences, the viruses belonging to viral genotypes were: genotype G (126), genotype D (23), genotype H (2), genotype F (2), genotype J (1), while one remained uncharacterized. Amino acid differences were detected between circulating strains and the Jeryl Lynn vaccine strains, although the majority of amino acid substitutions were genotype-specific. Fifty-one outbreaks were notified that included 324 confirmed mumps cases. Genotype G was the most frequent genotype detected. The family (35%), secondary schools (25%) and community outbreaks (18%) were the most frequent settings. CONCLUSIONS: Our study shows that genotype G viruses are the most prevalent in Catalonia. Most cases occurred in people who had received two doses of MMR, suggesting inadequate effectiveness of the Jeryl Lynn vaccine strain. The possible factors related are discussed.